1997
DOI: 10.1538/expanim.46.117
|View full text |Cite
|
Sign up to set email alerts
|

Process of the Development of T-2 Toxin-induced Apoptosis in the Lymphoid Organs of Mice.

Abstract: Female ICR:CD-1 mice orally treated with 10 mg/kg b.w. of T-2 toxin were killed at 1, 3, 6, 9, 12, 24 and 48 hr after treatment (HAT) and subjected to examination of the process of the development of T-2 toxin-induced apoptosis in the thymus and spleen. The early ultrastructural changes in lymphocytes characterized by shrinkage of the cell body and condensation of nuclear chromatin were detected at 3HAT in the thymus. The number of apoptotic lymphocytes observed by the in situ detection method for fragmented D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
10

Year Published

2001
2001
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
1
13
1
10
Order By: Relevance
“…In the cells treated with 0.2 µg/ml of T-2 toxin, cell viability began to decrease from 1 to 3 HAT when the level of fragmented DNA began to increase. These findings suggest that T-2 toxin can also induce apoptotic cell death in mouse thymocytes in vitro as reported in in vivo study 7 . In addition, a rapid increase in cfos mRNA expression was also observed prior to the development of T-2 toxin-induced apoptotic cell death in mouse thymocytes primary cultures as described in in vivo study 11 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the cells treated with 0.2 µg/ml of T-2 toxin, cell viability began to decrease from 1 to 3 HAT when the level of fragmented DNA began to increase. These findings suggest that T-2 toxin can also induce apoptotic cell death in mouse thymocytes in vitro as reported in in vivo study 7 . In addition, a rapid increase in cfos mRNA expression was also observed prior to the development of T-2 toxin-induced apoptotic cell death in mouse thymocytes primary cultures as described in in vivo study 11 .…”
Section: Discussionsupporting
confidence: 82%
“…Oral, parenteral and cutaneous exposures of trichothecene mycotoxin produce lesions in hematopoietic, lymphoid and gastrointestinal tissues as well as functional suppression in reproductive organs [2][3][4][5] . Our reseach group first clarified that T-2 toxininduced death of lymphocytes in the thymus 6,7 , splenic white pulp 6,7 and Peyer's patches 8 is apoptosis. After that, our research group also confirmed that hematopoietic cells in the bone marrow and splenic red pulp 9 , and intestinal crypt epithelial cells 10 die through apoptosis following T-2 toxininoculation.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic radiomimetic effects of T-2 toxin were considered as a major cause of impaired protein synthesis. In vivo T-2 toxin induced DNA damage in chicken peripheral lymphocytes [5] and apoptosis in vivo in haematopoietic tissues, spleen, liver and intestinal crypts of mice [6][7][8]. T-2 toxin was found to be haematotoxic having its effects on bone marrow, circulating blood cells and haemostasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of studies on the genotoxicity of T-2 toxin in vitro, T-2 toxin can induce DNA single-strand breaks in primary hematocytes, thymic and spleen lymphocytes of BALB/c mouse (56), gene mutations and sister chromatide exchange in Chinese hamster V79 fibroblasts (65)(66)(67)(68), formation of micronucleus in Chinese hamster V79 fibroblasts (67), unscheduled DNA synthesis in human fibroblasts (69), and inhibition of intercellular communication in Chinese hamster V79 cells (70). In addition, T-2 toxin and related mycotoxins can induce apoptosis in vitro (49,71,72) and in vivo in haematopoietic tissue, spleen, liver and intestinal crypts of mice (73)(74)(75)(76). In chicken, apoptosis was detected in the thymus, but not in the spleen (57).…”
Section: Genotoxic and Cytotoxic Effectsmentioning
confidence: 99%